2017
DOI: 10.1038/s41598-017-11878-7
|View full text |Cite
|
Sign up to set email alerts
|

Intrafascial versus interfascial nerve sparing in radical prostatectomy for localized prostate cancer: a systematic review and meta-analysis

Abstract: The present study aimed to systematically evaluate the effectiveness and safety of the intrafascial and interfascial nerve sparing (ITR-NS and ITE-NS) radical prostatectomy. PubMed, Embase, and Cochrane Library databases were searched for eligible studies. Meta-analysis with random-effects model was performed. Six comparative trials were selected and embraced in this research, including one randomized controlled trial, three prospective comparative trials, and two retrospective comparative trials. With regard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…[ 15 ] Hong Weng et al suggested intrafacial to be superior to interfascial nerve sparing in terms of subsequent potency. [ 16 ] In the present study, we exclusively included intrafascial nerve dissection patients, keeping in mind its documented superiority over other methods. Comparing cautery and noncautery techniques has produced conflicting results, with Ahlering et al showing a benefit with the cautery-free technique,[ 17 ] but Samadi et al not demonstrating any benefit with the athermal technique in a larger study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 15 ] Hong Weng et al suggested intrafacial to be superior to interfascial nerve sparing in terms of subsequent potency. [ 16 ] In the present study, we exclusively included intrafascial nerve dissection patients, keeping in mind its documented superiority over other methods. Comparing cautery and noncautery techniques has produced conflicting results, with Ahlering et al showing a benefit with the cautery-free technique,[ 17 ] but Samadi et al not demonstrating any benefit with the athermal technique in a larger study.…”
Section: Discussionmentioning
confidence: 99%
“…Quantum of nerve sparing (unilateral or bilateral), presence of periprostatic adhesions, lateral traction on the nerves, cautery usage with bleeding, and trauma to the nerves were taken as defining parameters in IOPAG because prior literature shows these factors as possibly affecting potency outcomes. [ 3 4 5 6 7 8 ] Six yes or no questions were answered and scored as per Table 3 . Based on their scores, patients were risk stratified into Grades 1 to 4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then I 2 statistic and Chi-squared test will be used to assess the presence of statistical heterogeneity and calculate the heterogeneity severity. When P > .1, I 2 < 50%, it is considered that there is acceptable heterogeneity between the trials, and the fixed effect model will be chosen; [ 25 , 26 ] otherwise, the random effect model will be considered and we will try to explain the underlying cause of heterogeneity by subgroup or sensitivity analysis (see “Subgroup analysis and sensitivity analysis” section below). [ 27 ] If heterogeneity is high, the meta-analysis should be avoided.…”
Section: Methodsmentioning
confidence: 99%
“…A recent prospective and controlled research reported the morbility of incontinence at 12 month after RP was about 20% and that of ED was about 70% [3]. In order to promote the recovery of continence and potency, some modi cations and re nements on the technique of RP were developed and applied by numerous teams mainly based on the maximal preservation of periprostatic structures with the advancing understanding of the surrounding anatomy of prostate such as the neurovascular bundles (NVB),pelvic oor, urethral sphicnter muscle and the prostate fascia [4][5][6]. The cavernous nerves in NVB nally reaching the corpora cavernosa were directly related to potency.…”
Section: Introductionmentioning
confidence: 99%